Pencegahan Penyalahgunaan Narkotika Oleh Badan Narkotika Nasional Kota Pekanbaru Terhadap Pelajar di Kota Pekanbaru - Andri, Mulia; Effendi, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The development of world civilization are increasingly berkembangan towards modernisasi.Perkembangan which always brings changes in every facet of life seem more nyata.Seiring with that also forms of crime are also constantly keep abreast of the times and transformed into forms that increasingly sophisticated and diverse.Drugs (narcotics, psychotropic, and Drugs) is a term of law enforcement and masyarakat.Narkoba called dangerous, because it is not safe to use manusia.Oleh therefore, use, production, and circulation is regulated in the law undang.Barang who use and distribute outside provisions of the law, subject to criminal sanctions of imprisonment and fines. Because of the danger of dependency, use, and distribution of drugs regulated by law, namely Law No. 35 of 2009 on Narcotics.Based on the above to know what are the factors that cause crime drug abuse among students in the jurisdiction of the National Narcotics Agency Pekanbaru, What are the obstacles that dihadapin by the National Narcotics Agency Pekanbaru against the crime of drug abuse by students in the city of Pekanbaru, the efforts undertaken by national agencies na rkotika city of Pekanbaru in tackling criminal acts of drug abuse by students in the city of Pekanbaru.Terms of the method used, this research can be classified into types of juridical sociological research, which means reviewing the state of the existing problems in the field in associate with aspects applicable laws and governing problems tersebut.Karena in this study the authors directly conduct research on location or place which ditrliti to provide complete and clear picture of the problem under study.In general, there are several factors that led to the occurrence of a crime, the first is a factor that comes or there from the perpetrator that means that that predispose a person to commit a crime that arises from within the actors themselves were based on heredity and psychological (mental illness ). The second factor is the factors that are beyond the offender is a factor of households and the environment, While it has been given the authority in the enforcement of an issue of drugs, but in the prevention, combating abuse and illicit drug trafficking in the city of Pekanbaru still encounter obstacles in Caused by a variety of factorsKeywords: Prevention, Abuse, Drugs, Student